2019
DOI: 10.1542/hpeds.2019-0078
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Infant Car Seat Tolerance Screening Failure Within a Large Health Care System, 2014–2018

Abstract: To describe temporal trends in car seat tolerance screening (CSTS) failure within a large hospital system (2014-2018). METHODS: We conducted a retrospective cohort study using electronic medical record data for infants who underwent a CSTS. Our primary outcome measure was the CSTS failure rate. Covariates included year, CSTS location (well nursery or NICU), gestational age (GA), race, sex, birth weight, CSTS date, and age at CSTS. Associations of covariates with CSTS failure were examined by using x 2 tests, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Lower adherence to CSTS policies among term and low birth weight infants is a novel finding. Previous literature suggests that term and low birth weight infants have similar likelihood of CSTS failure as their preterm counterpoints (Bass, 2015 ; Davis, 2015 ; McLaurin-Jiang et al, 2019 ). This is likely due to decreased muscle tone, greater susceptibility to airway obstruction while seated semi-upright, and small size which complicates positioning in car seat.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Lower adherence to CSTS policies among term and low birth weight infants is a novel finding. Previous literature suggests that term and low birth weight infants have similar likelihood of CSTS failure as their preterm counterpoints (Bass, 2015 ; Davis, 2015 ; McLaurin-Jiang et al, 2019 ). This is likely due to decreased muscle tone, greater susceptibility to airway obstruction while seated semi-upright, and small size which complicates positioning in car seat.…”
Section: Discussionmentioning
confidence: 98%
“…Only one infant documented parents declining screening during this study period. Alternatively, when comparing premature Black infants to non-Black infants of the same gestational age, the Black infants are known to have improved respiratory outcomes (Jensen et al, 2018 ; Loftin et al, 2012 ; MacDorman & Gregory, 2015 ; McLaurin-Jiang et al, 2019 ). In addition, small epidemiologic studies have reported lower risk of CSTS failure among Black infants (Jensen et al, 2018 ; McLaurin-Jiang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations